Effects of environmental change on plant performance and plant-herbivore interactions - Prill, N (2014)
Global environmental change fundamentally affects plants and their interactions with other species, and this has profound impacts on communities and ultimately ecosystems. In order to understand the mechanisms involved, we need to elaborate on the combined effects of different global change drivers on multiple levels of plant organization, including the biochemical level (production of defence compounds), the whole organism, the population, and the plant-herbivore interaction level. This thesis investigates (1) the combined effects of factors related to climate change and habitat fragmentation on Brassica nigra and (2) the effects of Zn soil pollution on the heavy metal hyperaccumulator Noccaea caerulescens at these different levels. Common garden and greenhouse experiments with B. nigra applied drought stress and elevated CO2 to examine climate change impacts, while crossing treatments (inbreeding and between-population outbreeding) were used to investigate habitat fragmentation effects. Heterosis was lost under drought stress, and there were several interactive effects of the experimental treatments that varied within and among populations. In a greenhouse experiment with N. caerulescens, plants were grown on soil with different amounts of zinc. Plants had greater herbivore resistance when grown on Zn-amended soil, and invested more in herbivore tolerance when grown on soil without added Zn. In general, the results indicate that factors related to global environmental change have complex and interactive effects on different levels of plant organization. The findings are discussed in terms of their implications for ecology, evolution and conservation.